A Quantitative Examination and Comparison of the Ability of Australian Gentamicin Dosing Guidelines to Achieve Target Therapeutic Concentrations in Neonates - Luke E. Grzeskowiak; Sheree Wynne; Michael J. Stark (Antibiotics)
Background: Effective gentamicin dosing is crucial to the survival of neonates with suspected sepsis but requires a careful balance between attaining both effective peak and safe trough concentrations. We aimed to systematically compare existing gentamicin dosing guidelines for neonates in Australia to determine the extent to which they reach therapeutic targets. Methods: Simulations of a single gentamicin dose to a virtual representative neonatal population according to each Australian guideline were performed using population pharmacokinetic modelling. We determined the proportion of neonates who would achieve peak gentamicin concentrations of ≥5 or ≥10 mg/L and trough concentrations of ≤1 or ≤2 mg/L. We calculated the probability of target attainment (PTA) according to gestation at birth (22 to 40 weeks) and postnatal age (1–7, 8–14, 15–21, 22–28 days). Results: Five unique dosing guidelines were identified. Guidelines varied considerably with respect to dose (4.5 to 7 mg/kg), dosing interval (24 to 48 h), and characteristics used to individualise dosing regimens (e.g., gestation at birth and postnatal age). Guidelines were satisfactory in routinely achieving effective peak concentrations ≥ 5 mg/L, but PTAs for effective peak concentrations ≥ 10 mg/L varied considerably from 5% to 100% based on dose, gestation, and postnatal age. PTAs for trough concentrations ≤ 1 mg/L ranged from 0% to 100%, being lowest among extremely preterm infants. Conclusions: Current Australian gentamicin guidelines demonstrate significant variability in their ability to achieve defined therapeutic targets, necessitating efforts to improve standardisation of dosing recommendations. Further research to define optimal pharmacodynamic targets in neonates with respect to clinical outcomes are also urgently warranted.